War Metaphors in Nigerian Pidgin Political News Coverage (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study investigates the types of conceptual metaphors of war in Nigerian Pidgin news coverage; it focusses on the BBC Pidgin political news of September to December 2023. Grounded in Conceptual Metaphor Theory (CMT) and using a qualitative approach with purposive and convenient sampling techniques, the study identified and analysed eight distinct conceptual metaphors which depicted politics, political events and electoral court cases as battle or war. The conceptual metaphors are used in order to simplify complex political and legal processes; they make complex political issues more accessible and relatable to readers. Key findings reveal that metaphors are used to map abstract political concepts onto familiar domains of battle, war, physical struggles and explosion. Beyond shaping public perception, this study highlights implications for political discourse in multilingual societies; it shows Nigerian Pidgin’s metaphorical language and bridges communication gap between government and grassroots audiences in political communication. By situating the analysis within literature on metaphor in pidgin and creole languages, this research contributes to understanding how creole and pidgin languages uniquely mediate political narratives, particularly in postcolonial contexts. Further, the study emphasises the role of Nigerian Pidgin not only as a lingua franca; but as a dynamic tool for framing sociopolitical realities; it offers insights for scholars of media, linguistics and African political communication.
Keywords: Conceptual Metaphors; Conceptual Mappings; Nigerian Pidgin; Political Discourse